Small Intestinal Bacterial Overgrowth in Subclinical Hypothyroidism of Pregnant Women - Wang, Biao; Xu, Yajuan; Hou, Xiaofeng; Li, Jingjing; Cai, Yanjun; Hao, Yingqi; Ouyang, Qian; Wu, Bo; Sun, Zongzong; Zhang, Miao; Ban, Yanjie (Frontiers in Endocrinology, 2021)
Objective To evaluate the small intestinal bacterial overgrowth (SIBO) of subclinical hypothyroidism of pregnant women, and explore their possible relevance. Methods In total, 224 pregnant women with subclinical hypothyroidism during pregnancy (study group) and 196 pregnant women whose thyroid function was normal (control group) were enrolled in this study. Lactulose-based hydrogen and methane breath test was performed to evaluate the growth of intestinal bacteria. The serum-free thyroid hormone (FT4), thyroid-stimulating hormone (TSH), thyroid peroxidase antibody (TPOAb), body mass index (BMI) and gastrointestinal symptoms were detected and recorded. Results The positive rates of SIBO were 56.7% and 31.6% in study group and control group, respectively. The levels of C response protein (CRP), abdominal distension and constipation in study group were higher than those in the control group. The risk of abdominal distension and constipation in SIBO-positive pregnant women were higher than that in SIBO-negative pregnant women, and the BMI of SIBO-positive patients in the two groups was lower than that of SIBO-negative patients in each group. In addition, the TPOAb-positive rate and TSH levels were higher but the FT4 level was lower in SIBO-positive patients compared to SIBO-negative patients in study group. Conclusion The occurrence of subclinical hypothyroidism is related to SIBO, and the excessive growth of small intestinal bacteria may affect gastrointestinal symptoms. Clinical Trial http://www.chictr.org.cn/index.aspx, identifier ChiCTR1900026326.